2013
DOI: 10.5301/jva.5000126
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided Endovascular Treatment for Vascular Access Malfunction: Results in 4896 Cases

Abstract: Ultrasound-guided PTA for arteriovenous fistula malfunction could be used as a substitute for fluoroscopy-guided PTA, and enables the use of safe and rapid intervention techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 11 publications
2
39
0
2
Order By: Relevance
“…However, application of ultrasound imaging during endovascular procedures on the subclavian vein and brachiocephalic trunk was also described. In such situations a micro-covex probe is used, which enables visualization of vessels through intercostal spaces [9]. Ultrasound allows for precise determination of puncture site, making it easier to conduct the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, application of ultrasound imaging during endovascular procedures on the subclavian vein and brachiocephalic trunk was also described. In such situations a micro-covex probe is used, which enables visualization of vessels through intercostal spaces [9]. Ultrasound allows for precise determination of puncture site, making it easier to conduct the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness ranged between 92 and 97% depending on indications and location of the lesion [4,9]. In our opinion, ultrasound control of dialysis fistula repairs will be used increasingly more often due to frequent indications, effectiveness and small costs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, vascular access intervention therapy (VAIVT) has become one of the established therapy options for resolving VAF [1,[6][7][8][9][10][11]. Although VAIVT is less invasive than surgical reconstruction [7,[12][13][14], information on prevention of VAF after VAIVT is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Procedures were first performed in the cathlab under sonography guidance, limiting the use of fluoroscopy to bail-out procedure [1][2][3][4][5][6]. After exclusion of cases with central vein stenosis (where duplex scan does not provide sufficient image quality) three authors then investigated the feasibility of AVFs angioplasty or AVFs balloon-assisted maturation in an office-based setting with very encouraging results [1][2][3]. Overall these first studies demonstrated the feasibility of this technique without experiencing major adverse event [4][5][6].…”
Section: Introductionmentioning
confidence: 99%